Green and environment-friendly pH-responsive corrosion inhibitor as well as preparation method and application thereof

Through the synergy between green tea polyphenols, graphene oxide nanosheets and pH-responsive polymer microcapsules, a green and environmentally friendly pH-responsive corrosion inhibitor was developed, which solved the problem of unstable traditional corrosion inhibitors in high temperature, high salt and high oxidation environments, and achieved efficient, long-term and environmentally friendly corrosion resistance.

CN119506890APending Publication Date: 2025-02-25武汉钢铁有限公司
View PDF 0 Cites 4 Cited by

Patent Information

Application Number
CN202411699215.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing corrosion inhibitors are unstable in high temperature, high salt and high oxidation environments, and traditional corrosion inhibitors pose a threat to the environment and human health, making it difficult to take into account both temperature resistance, oxidation resistance and environmental friendliness.

Method used

The synergistic effect of green tea polyphenols and graphene oxide nanosheets is used to combine pH-responsive polymer corrosion-inhibiting microcapsules and β-cyclodextrin/corrosion-inhibiting salt inclusions to form a green and environmentally friendly pH-responsive corrosion-inhibiting agent. This corrosion inhibitor improves stability and long-term effectiveness in high temperature and high oxidation environments through the intelligent self-healing mechanism of microcapsules and the synergistic effect of multiple components.

Benefits of technology

It achieves stability in high temperature, oxygen-containing and high salinity environments, provides anti-corrosion protection for a long time, reduces the burden on the environment, and improves the durability and anti-oxidation effect of the corrosion inhibitor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005152840060000101
    Figure BDA0005152840060000101
Patent Text Reader

Abstract

The invention belongs to the technical field of water treatment, and discloses a green and environment-friendly pH-responsive corrosion inhibitor as well as a preparation method and application thereof. The corrosion inhibitor comprises the following raw materials in parts by mass: 25-30 parts of green tea polyphenol, 10-15 parts of graphene oxide nanosheets, 15-25 parts of pH response type polymer corrosion inhibition microcapsules, 5-10 parts of a beta-cyclodextrin / corrosion inhibition salt inclusion compound, 5-10 parts of an amino acid derivative polymer, 3-5 parts of a thickening agent, 180-450 parts of a solvent, and an antioxidant accounting for 0.01-0.05% of the total mass of the raw materials. And a pH regulator is added to regulate the pH of the corrosion inhibitor to 7-8. According to the corrosion inhibitor, plant extracts and non-toxic chemical substances are adopted as main components, the requirements of environment-friendly materials are met, and under the synergistic effect of all the components, the corrosion inhibitor can keep stable in a high-temperature, oxygen-containing and high-salinity environment, and anti-corrosion protection can be provided for a long time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of water treatment, and in particular relates to a green and environmentally friendly pH responsive corrosion inhibitor and a preparation method and application thereof. Background Art

[0002] The composition of water in industrial systems has a significant impact on the use of the system. When water contains corrosive ions such as chloride ions and sulfate ions, it is very easy to react with metal surfaces, causing serious corrosion of equipment and pipelines. Long-term corrosion will not only reduce the operating efficiency of equipment and increase maintenance costs, but may also cause safety hazards. In order to deal with corrosion problems, the commonly used treatment methods include the use of corrosion-resistant materials, anti-corrosion coatings, electrochemical protection, and the addition of corrosion inhibitors. In comparison, the addition of corrosion inhibitors is the simplest and most economical treatment method.

[0003] Although traditional corrosion inhibitors such as chromates and phosphates have good corrosion inhibition effects, their use is very harmful to the environment. In particular, chromates are gradually banned worldwide due to their strong toxicity and difficulty in degradation. Therefore, the focus of research and development in recent years has gradually shifted to green and environmentally friendly corrosion inhibitors. In addition, the complex chemical environment of high temperature and high salt in water treatment systems also requires corrosion inhibitors to have excellent temperature resistance, oxidation resistance, compatibility with a variety of corrosive media, and long-term effectiveness. However, there is currently a lack of corrosion inhibitors that meet the above requirements. Summary of the invention

[0004] The technical problem to be solved by the present invention is to provide a green and environmentally friendly pH-responsive corrosion inhibitor and its preparation method and application in view of the shortcomings of the prior art. The corrosion inhibitor uses plant extracts and non-toxic chemicals as main ingredients, meets the requirements of environmentally friendly materials, and under the synergistic effect of various components, the corrosion inhibitor can remain stable in high temperature, oxygen-containing and high-salinity environments, and provide long-term anti-corrosion protection.

[0005] In order to solve the technical problem proposed by the present invention, the present invention provides a green and environmentally friendly pH-responsive corrosion inhibitor, comprising the following raw materials in parts by weight: 25 to 30 parts of green tea polyphenols, 10 to 15 parts of graphene oxide nanosheets, 15 to 25 parts of pH-responsive polymer corrosion-inhibiting microcapsules, 5 to 10 parts of β-cyclodextrin / corrosion-inhibiting salt inclusion complexes, 5 to 10 parts of amino acid-derived polymers, 3 to 5 parts of thickeners, 180 to 450 parts of solvents, and an antioxidant in an amount of 0.01 to 0.05% of the total weight of the above raw materials, and a pH adjuster to adjust the pH of the corrosion inhibitor to 7 to 8.

[0006] In the above scheme, the diameter of the graphene oxide nanosheets is 100nm to 1μm.

[0007] In the above scheme, the pH-responsive polymer corrosion-inhibiting microcapsules are microcapsules formed with zinc salt and molybdate as capsule core and hydrophobic pH-responsive polymer as capsule wall, and the particle size thereof is 100 nm to 1 μm.

[0008] In the above scheme, the preparation method of the pH-responsive polymer corrosion-inhibiting microcapsules comprises the following steps:

[0009] 1) dissolving a hydrophobic pH-responsive polymer in an organic solvent, and then adding zinc salt and molybdate and mixing them evenly to form an oil phase;

[0010] 2) dissolving the emulsifier in water and adjusting the pH of the solution to 7-8 to form an aqueous phase;

[0011] 3) dropping the oil phase into the water phase and stirring at high speed for emulsification, then reducing the stirring speed for solidification, and finally separating the solid and the liquid, and drying the obtained solid to obtain pH-responsive polymer corrosion-inhibiting microcapsules.

[0012] Furthermore, the hydrophobic pH-responsive polymer is one of polyacrylic acid (PAA), polylactic acid-glycolic acid copolymer (PLGA), polymethyl methacrylate (PMMA), and polyethylene oxide-polylactic acid copolymer (PEO-PLA).

[0013] Furthermore, the organic solvent is one of dichloromethane and ethyl acetate.

[0014] Furthermore, the zinc salt is one of zinc acetate and zinc sulfate.

[0015] Furthermore, the molybdate is one of sodium molybdate and ammonium molybdate.

[0016] Furthermore, in the oil phase, the mass concentration of the hydrophobic pH responsive polymer is 100-200 g / L, the mass concentration of the zinc salt is 30-50 g / L, and the mass concentration of the molybdate is 30-50 g / L.

[0017] Furthermore, the emulsifier is one of polyvinyl alcohol and polyethylene glycol.

[0018] Furthermore, in the water phase, the mass concentration of the emulsifier is 10 to 20 g / L.

[0019] Furthermore, in step 2), the pH of the solution is adjusted by hydrochloric acid or NaOH solution.

[0020] Furthermore, the volume ratio of the oil phase to the water phase is 1:(5-8).

[0021] Furthermore, in the emulsification process, the stirring speed is controlled to be 800-1200 rpm, the emulsification temperature is controlled to be 25-30° C., and the emulsification time is controlled to be 10-20 min.

[0022] Furthermore, in the curing process, the stirring speed is controlled to be 400-600 rpm, the curing temperature is controlled to be 25-27° C., and the curing time is controlled to be 2-3 hours.

[0023] Furthermore, in step 3), the drying is vacuum drying, the drying temperature is 40-50° C., and the drying time is 4-6 hours.

[0024] In the above scheme, the particle size of the β-cyclodextrin / corrosion-inhibiting salt inclusion complex is 1 to 10 μm.

[0025] In the above scheme, the preparation method of the β-cyclodextrin / corrosion-inhibiting salt inclusion compound comprises the following steps:

[0026] (1) dissolving β-cyclodextrin in water to form a cyclodextrin solution, and then adding a corrosion-inhibiting salt and stirring thoroughly to form a mixed solution;

[0027] (2) After adjusting the pH of the mixed solution to 5-7, heating and stirring are performed to carry out inclusion reaction. After the reaction is completed, cooling is performed, an ethanol solution is added to precipitate, and the precipitate is dried to obtain a β-cyclodextrin / corrosion inhibition salt inclusion complex.

[0028] Furthermore, in the cyclodextrin solution, the mass concentration of β-cyclodextrin is 100-150 g / L.

[0029] Furthermore, the corrosion-inhibiting salt is one of zinc salt and molybdate.

[0030] Furthermore, the mass ratio of the corrosion-inhibiting salt to β-cyclodextrin is (5-10):100.

[0031] Furthermore, in step (1), the stirring speed after the corrosion-inhibiting salt is added is 300 to 500 rpm, and the stirring time is 45 to 60 min.

[0032] Furthermore, in step (2), the pH of the mixed solution is adjusted by citric acid or sodium bicarbonate solution.

[0033] Furthermore, the reaction temperature of the inclusion reaction is 40-50° C., and the reaction time is 2-4 hours.

[0034] Furthermore, the volume concentration of the ethanol solution is 50-70%, the volume of the ethanol solution is 1-1.5 times the volume of the mixed solution, and the precipitation time is 1-2 hours.

[0035] Furthermore, in step (2), the drying is vacuum drying, the drying temperature is 40 to 50° C., and the drying time is 6 to 8 hours.

[0036] In the above scheme, the amino acid-derived polymer is one of polyglutamic acid and polyaspartic acid.

[0037] In the above scheme, the thickener is carboxymethyl cellulose (CMC).

[0038] In the above scheme, the solvent is at least one of water and alcohol.

[0039] Furthermore, the alcohol is at least one of ethanol and isopropanol.

[0040] In the above scheme, the antioxidant is one of ascorbic acid and vitamin E.

[0041] In the above scheme, the pH adjuster is one of citric acid and sodium bicarbonate.

[0042] The present invention also provides a method for preparing a green and environmentally friendly pH-responsive corrosion inhibitor, comprising the following steps:

[0043] S1, adding an antioxidant to water, then heating it to dissolve green tea polyphenols therein, and then adding β-cyclodextrin / corrosion-inhibiting salt inclusion complex and stirring thoroughly to obtain a first solution;

[0044] S2, ultrasonically dispersing graphene oxide nanosheets in water or alcohol, adding the resultant to the first solution and stirring the solution sufficiently to obtain a second solution;

[0045] S3, adding pH-responsive polymer corrosion-inhibiting microcapsules to the second solution and stirring evenly, then sequentially adding thickener and amino acid-derived polymer and stirring evenly, finally adding the remaining solvent, and using a pH adjuster to adjust the pH of the solution to 7-8, to obtain a green and environmentally friendly pH-responsive corrosion inhibitor.

[0046] In the above scheme, in step S1, the mass ratio of water to green tea polyphenols is (3-5):1.

[0047] In the above scheme, in step S1, the heating temperature is 40-50°C, and this temperature can be maintained until the preparation of the first solution is completed.

[0048] In the above scheme, in step S1, the stirring rate after the addition of the β-cyclodextrin / corrosion-inhibiting salt inclusion complex is 200-400 rpm, and the stirring time is 20-30 min.

[0049] In the above scheme, in step S2, when the graphene oxide nanosheets are prepared in a hydrophilic form and have hydrophilic functional groups on the surface, water is used as the dispersion medium; when the graphene oxide nanosheets have hydrophobic functional groups on the surface or have poor dispersion stability, alcohol is used as the dispersion medium.

[0050] In the above scheme, in step S2, the mass ratio of graphene oxide nanosheets to water or alcohol is 1:(10-20).

[0051] In the above scheme, in step S2, the ultrasonic dispersion time is 15 to 20 minutes.

[0052] In the above scheme, in step S2, the stirring rate after the graphene oxide nanosheets are added to the first solution is 200 to 400 rpm, and the stirring time is 1.5 to 2 hours.

[0053] In the above scheme, in step S3, when the pH-responsive polymer corrosion-inhibiting microcapsules are added, the solution temperature is controlled to be 35-45° C., the stirring rate is 100-200 rpm, and the stirring time is 45-60 min.

[0054] In the above scheme, in step S3, when the thickener and the amino acid derivative polymer are added, the solution may not be heated, and the stirring rate is controlled to be 200-400 rpm. The thickener is stirred for 20-30 minutes after addition, and the amino acid derivative polymer is stirred for 30-45 minutes after addition.

[0055] The present invention also provides an application of a green and environmentally friendly pH-responsive corrosion inhibitor in corrosion inhibition of a water system, and the application method is: adding the green and environmentally friendly pH-responsive corrosion inhibitor into the water system.

[0056] In the above scheme, the dosage of the green and environmentally friendly pH-responsive corrosion inhibitor is 100-500ppm.

[0057] In the above scheme, the temperature in the water system is 10-80°C, the pH is 6.5-8.5, the dissolved oxygen concentration is 5-8 mg / L, and the corrosive medium contained is one or more of chloride, sulfate, and fluoride, the chloride concentration is ≤10000 mg / L, the sulfate concentration is ≤5000 mg / L, and the fluoride concentration is ≤100 mg / L.

[0058] In the above scheme, after the green and environmentally friendly pH-responsive corrosion inhibitor is added, the corrosion inhibitor can be evenly distributed in the entire water system by starting the circulation pump to circulate for 1 to 2 hours to ensure that the corrosion inhibitor is evenly distributed and forms a protective film on the pipe wall of the water system equipment.

[0059] In the above scheme, after the green and environmentally friendly pH-responsive corrosion inhibitor is added, the pH in the water system can be regularly tested. When the pH in the water system deviates significantly, citric acid or sodium bicarbonate can be added to return it to between 6.5 and 8.5 to maintain the activity of the corrosion inhibitor.

[0060] The technical concept of the present invention is:

[0061] 1. Design on pH-responsive polymer corrosion inhibition microcapsules:

[0062] The core corrosion inhibition components are zinc salt and molybdenum salt, which are uniformly coated in a hydrophobic pH-responsive polymer through oil phase emulsification technology to form a core-shell structure. The microcapsules respond to local pH changes and release the corrosion inhibitor, effectively realizing intelligent self-repair.

[0063] 2. Design on β-cyclodextrin / corrosion inhibition salt inclusion complex:

[0064] By utilizing the hydrophobic inner cavity and hydrophilic outer edge of cyclodextrin molecules, a stable inclusion complex is formed with the active substance zinc salt or molybdenum salt, which enhances the solubility and stability of the corrosion inhibitor. The purity and efficacy of the inclusion complex are ensured through partial ethanol precipitation extraction.

[0065] 3. Design of green and environmentally friendly pH-responsive corrosion inhibitor:

[0066] ① Synergistic effect of green tea polyphenols and graphene oxide: The combination of the two can form a double-layer barrier structure on the metal surface. The adsorption film of green tea polyphenols can serve as a chemical barrier, while the two-dimensional structure of graphene oxide fills microcracks to form a physical barrier. The double-layer structure can effectively improve the oxidation resistance and temperature resistance of the corrosion inhibitor, while preventing the infiltration of external corrosive media.

[0067] ②Synergistic effect of pH-responsive polymer corrosion-inhibiting microcapsules and amino acid-derived polymers: pH-responsive microcapsules release corrosion inhibitors when pH changes due to local corrosion, and amino acid-derived polymers then form chelates around metal ions (such as Fe2+ and Fe3+), further preventing corrosion reactions from occurring. This combined effect can enhance the long-term stability of corrosion inhibitors in high temperature and oxidative environments, while achieving self-repairing functions and extending the effective life of corrosion inhibitors.

[0068] ③ Combination of β-cyclodextrin / corrosion-inhibiting salt inclusion complex and thickener: Cyclodextrin inclusion complex can not only improve the stability of corrosion inhibitor in high-salt environment, but also improve the adhesion of corrosion inhibitor on metal surface when used in combination with thickener, and effectively prevent corrosion inhibitor from being washed away by fluid. The presence of thickener can keep corrosion inhibitor evenly distributed in high-flow environment, and improve its long-term effectiveness in cooling water system.

[0069] Compared with the prior art, the present invention has the following beneficial effects:

[0070] 1) Green and environmentally friendly: The corrosion inhibitor of the present invention uses plant extracts (such as green tea polyphenols) and non-toxic chemicals as main ingredients, which meets the requirements of environmentally friendly materials, avoids the harm of toxic compounds in traditional corrosion inhibitors to the environment and human body, and greatly reduces the burden on the environment.

[0071] 2) Intelligent self-repair function: By introducing pH-responsive microcapsules, when the metal surface causes local pH changes due to corrosion, the microcapsules will actively release corrosion inhibitors to fill the corrosion points, thereby achieving self-repair function. This response mechanism greatly improves the durability and antioxidant effect of the corrosion inhibitor, allowing it to work effectively in high temperature and oxidative environments, and is particularly suitable for metal equipment exposed to corrosive environments for a long time.

[0072] 3) Long-lasting and durable anti-corrosion effect: Under the synergistic effect of various components, the corrosion inhibitor of the present invention can remain stable in high temperature, oxygen-containing and high-salinity environments, and provide long-term corrosion protection. In particular, the synergistic barrier effect of graphene oxide and green tea polyphenols, the uniform distribution of cyclodextrin complexes and the self-repair mechanism of microcapsules enable the corrosion inhibitor to maintain a long-term corrosion inhibition effect in harsh environments, reduce the frequency of replenishment, and extend the service life of equipment. DETAILED DESCRIPTION

[0073] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.

[0074] In the following examples, the diameter of the graphene oxide nanosheets used is 100 nm to 1 μm.

[0075] Example 1

[0076] A green and environmentally friendly pH responsive corrosion inhibitor comprises the following raw materials in parts by weight: 25 parts of green tea polyphenols, 10 parts of graphene oxide nanosheets, 15 parts of pH responsive polymer corrosion inhibition microcapsules, 5 parts of beta-cyclodextrin / corrosion inhibition salt inclusion compound, 5 parts of polyaspartic acid, 3 parts of carboxymethyl cellulose, 270 parts of solvent (100 parts of water, 120 parts of ethanol, 50 parts of isopropanol), ascorbic acid accounting for 0.01% of the total weight of the above raw materials, and citric acid is added to adjust the pH of the corrosion inhibitor to 7.

[0077] In this embodiment, the preparation method of pH responsive polymer corrosion inhibition microcapsules includes the following steps:

[0078] 1) dissolving polylactic acid-co-glycolic acid (PLGA) in dichloromethane, and then adding zinc acetate and sodium molybdate and mixing evenly to form an oil phase; in the oil phase, the mass concentration of polylactic acid-co-glycolic acid (PLGA) is 150 g / L, the mass concentration of zinc acetate is 40 g / L, and the mass concentration of sodium molybdate is 30 g / L;

[0079] 2) dissolving polyvinyl alcohol in water, and adjusting the pH of the solution to 7.2 with 0.1 mol / L dilute hydrochloric acid to form an aqueous phase; the mass concentration of polyvinyl alcohol in the aqueous phase is 12 g / L;

[0080] 3) The oil phase is added dropwise to the water phase with a volume ratio of 1:6, and the mixture is stirred at a high speed of 1000 rpm for 15 min at 27°C for emulsification, and then the stirring speed is reduced to 500 rpm and the temperature is reduced to 25°C for 2.5 h for solidification. Finally, the solid-liquid separation is performed, and the obtained solid is vacuum dried at 45°C for 5 h to obtain pH-responsive polymer corrosion-inhibiting microcapsules with a particle size of 100 nm to 1 μm.

[0081] In this embodiment, the preparation method of β-cyclodextrin / corrosion-inhibiting salt inclusion compound comprises the following steps:

[0082] (1) dissolving β-cyclodextrin in water to form a cyclodextrin solution with a mass concentration of 120 g / L, then adding zinc acetate, the mass ratio of zinc acetate to β-cyclodextrin being 5:100, and stirring at a speed of 400 rpm for 50 min to form a mixed solution;

[0083] (2) After adjusting the pH of the mixed solution to 5.5 using a sodium bicarbonate solution, the solution was heated to 45° C. and stirred for 3 h for inclusion reaction. After the reaction was completed, the solution was cooled, and then an ethanol solution with a volume concentration of 60% and a volume ratio of 1.2 times the volume of the mixed solution was added and allowed to stand for 1.5 h for precipitation. The precipitate was vacuum dried at 45° C. for 7 h to obtain a β-cyclodextrin / corrosion-inhibiting salt inclusion complex with a particle size of 1 to 10 μm.

[0084] The preparation method of the green and environmentally friendly pH-responsive corrosion inhibitor in this embodiment comprises the following steps:

[0085] S1, adding ascorbic acid to water, then heating to 42° C. to dissolve green tea polyphenols therein, then adding β-cyclodextrin / corrosion-inhibiting salt inclusion complex, and stirring at 200 rpm for 20 min to obtain a first solution;

[0086] S2, ultrasonically dispersing the graphene oxide nanosheets in ethanol for 15 min, then adding the nanosheets into the first solution, and stirring at 200 rpm for 1.5 h to obtain a second solution;

[0087] S3, control the second solution to 35°C, add pH-responsive polymer corrosion-inhibiting microcapsules thereto, stir at 100 rpm for 45 min, then add carboxymethyl cellulose and stir for 20 min, then add polyaspartic acid and stir for 30 min, finally add isopropanol, and use citric acid to adjust the solution pH to 7 to obtain a green and environmentally friendly pH-responsive corrosion inhibitor.

[0088] Example 2

[0089] A green and environmentally friendly pH responsive corrosion inhibitor comprises the following raw materials in parts by weight: 27 parts of green tea polyphenols, 12 parts of graphene oxide nanosheets, 20 parts of pH responsive polymer corrosion inhibition microcapsules, 7 parts of beta-cyclodextrin / corrosion inhibition salt inclusion complex, 7 parts of polyglutamic acid, 4 parts of carboxymethyl cellulose, 390 parts of solvent (135 parts of water, 180 parts of ethanol, 75 parts of isopropanol), 0.03% of the total weight of the above raw materials is added with vitamin E, and sodium bicarbonate is added to adjust the pH of the corrosion inhibitor to 7.5.

[0090] In this embodiment, the preparation method of pH responsive polymer corrosion inhibition microcapsules includes the following steps:

[0091] 1) dissolving polymethyl methacrylate (PMMA) in ethyl acetate, adding zinc sulfate and ammonium molybdate and mixing evenly to form an oil phase; in the oil phase, the mass concentration of polymethyl methacrylate (PMMA) is 180 g / L, the mass concentration of zinc sulfate is 35 g / L, and the mass concentration of ammonium molybdate is 40 g / L;

[0092] 2) dissolving polyethylene glycol in water, and adjusting the pH of the solution to 7.8 with a 0.1 mol / L dilute NaOH solution to form an aqueous phase; the mass concentration of polyethylene glycol in the aqueous phase is 15 g / L;

[0093] 3) The oil phase is added dropwise to the water phase with a volume ratio of 1:7, and the mixture is stirred at a high speed of 1200 rpm for 20 min at 30°C for emulsification, and then the stirring speed is reduced to 600 rpm and the temperature is reduced to 27°C for 3 h for solidification, and finally the solid-liquid separation is performed, and the obtained solid is vacuum dried at 50°C for 6 h to obtain pH-responsive polymer corrosion-inhibiting microcapsules with a particle size of 100 nm to 1 μm.

[0094] In this embodiment, the preparation method of β-cyclodextrin / corrosion-inhibiting salt inclusion compound comprises the following steps:

[0095] (1) dissolving β-cyclodextrin in water to form a cyclodextrin solution with a mass concentration of 130 g / L, then adding sodium molybdate, the mass ratio of sodium molybdate to β-cyclodextrin being 7:100, and stirring at a speed of 450 rpm for 60 min to form a mixed solution;

[0096] (2) After adjusting the pH of the mixed solution to 6 using a citric acid solution, the solution was heated to 50°C and stirred for 4 hours for inclusion reaction. After the reaction was completed, the solution was cooled, and then an ethanol solution with a volume concentration of 70% and a volume volume of 1.5 times the volume of the mixed solution was added and allowed to stand for 2 hours for precipitation. The precipitate was vacuum dried at 50°C for 8 hours to obtain a β-cyclodextrin / corrosion-inhibiting salt inclusion complex with a particle size of 1 to 10 μm.

[0097] The preparation method of the green and environmentally friendly pH-responsive corrosion inhibitor in this embodiment comprises the following steps:

[0098] S1, adding vitamin E to water, then heating to 45° C. to dissolve green tea polyphenols therein, then adding β-cyclodextrin / corrosion-inhibiting salt inclusion complex, and stirring at 300 rpm for 25 min to obtain a first solution;

[0099] S2, ultrasonically dispersing the graphene oxide nanosheets in ethanol for 18 min, then adding the nanosheets into the first solution, and stirring at 300 rpm for 1.5 h to obtain a second solution;

[0100] S3, control the second solution to 40°C, add pH-responsive polymer corrosion-inhibiting microcapsules thereto, stir at 150 rpm for 50 min, then add carboxymethyl cellulose and stir for 30 min, then add polyglutamic acid and stir for 40 min, finally add isopropanol, and use sodium bicarbonate to adjust the pH of the solution to 7.5 to obtain a green and environmentally friendly pH-responsive corrosion inhibitor.

[0101] Example 3

[0102] A green and environmentally friendly pH responsive corrosion inhibitor comprises the following raw materials in parts by weight: 30 parts of green tea polyphenols, 15 parts of graphene oxide nanosheets, 25 parts of pH responsive polymer corrosion inhibition microcapsules, 10 parts of beta-cyclodextrin / corrosion inhibition salt inclusion complex, 10 parts of polyglutamic acid, 5 parts of carboxymethyl cellulose, 385 parts of solvent (135 parts of water, 150 parts of ethanol, 100 parts of isopropanol), 0.05% of the total weight of the above raw materials is added with vitamin E, and sodium bicarbonate is added to adjust the pH of the corrosion inhibitor to 8.

[0103] In this embodiment, the preparation method of pH responsive polymer corrosion inhibition microcapsules includes the following steps:

[0104] 1) dissolving polyacrylic acid (PAA) in dichloromethane, adding zinc acetate and sodium molybdate and mixing evenly to form an oil phase; in the oil phase, the mass concentration of polyacrylic acid (PAA) is 200 g / L, the mass concentration of zinc acetate is 50 g / L, and the mass concentration of sodium molybdate is 50 g / L;

[0105] 2) dissolving polyvinyl alcohol in water, and adjusting the pH of the solution to 7.5 with 0.1 mol / L dilute hydrochloric acid to form an aqueous phase; the mass concentration of polyvinyl alcohol in the aqueous phase is 18 g / L;

[0106] 3) The oil phase is added dropwise to the water phase with a volume ratio of 1:5, and the mixture is stirred at a high speed of 800 rpm for 10 min at 25°C for emulsification, and then the stirring speed is reduced to 400 rpm and maintained for 2 h for solidification. Finally, the solid-liquid separation is performed, and the obtained solid is vacuum dried at 40°C for 4 h to obtain pH-responsive polymer corrosion-inhibiting microcapsules with a particle size of 100 nm to 1 μm.

[0107] In this embodiment, the preparation method of β-cyclodextrin / corrosion-inhibiting salt inclusion compound comprises the following steps:

[0108] (1) dissolving β-cyclodextrin in water to form a cyclodextrin solution with a mass concentration of 150 g / L, then adding zinc sulfate, the mass ratio of zinc sulfate to β-cyclodextrin being 10:100, and stirring at a speed of 500 rpm for 45 min to form a mixed solution;

[0109] (2) After adjusting the pH of the mixed solution to 6.5 using a sodium bicarbonate solution, the solution was heated to 40° C. and stirred for 2 h for inclusion reaction. After the reaction was completed, the solution was cooled, and then a 50% ethanol solution with a volume concentration of 1 times the volume of the mixed solution was added and allowed to stand for 1 h for precipitation. The precipitate was vacuum dried at 40° C. for 6 h to obtain a β-cyclodextrin / corrosion inhibition salt inclusion complex with a particle size of 1 to 10 μm.

[0110] The preparation method of the green and environmentally friendly pH-responsive corrosion inhibitor in this embodiment comprises the following steps:

[0111] S1, adding vitamin E to water, then heating to 50° C. to dissolve green tea polyphenols therein, then adding β-cyclodextrin / corrosion-inhibiting salt inclusion complex, and stirring at 400 rpm for 30 min to obtain a first solution;

[0112] S2, ultrasonically dispersing graphene oxide nanosheets in ethanol for 20 min, then adding the nanosheets into the first solution, and stirring at 400 rpm for 2 h to obtain a second solution;

[0113] S3, controlling the temperature of the second solution to 45°C, adding pH-responsive polymer corrosion-inhibiting microcapsules thereto, stirring at 200 rpm for 60 min, then adding carboxymethyl cellulose and stirring for 30 min, then adding polyglutamic acid and stirring for 45 min, finally adding isopropanol, and using sodium bicarbonate to adjust the pH of the solution to 8, to obtain a green and environmentally friendly pH-responsive corrosion inhibitor.

[0114] Comparative Example 1

[0115] Comparative Example 1 is a commercially available phosphate corrosion inhibitor.

[0116] Comparative Example 2

[0117] Comparative Example 2 is a commercially available benzotriazole corrosion inhibitor.

[0118] Application Examples

[0119] The corrosion inhibitors in the embodiments and comparative examples were respectively applied to the water system. The application method was as follows: adding the corrosion inhibitor to the water system, starting a circulation pump to circulate for 1 to 2 hours, and evenly distributing the corrosion inhibitor in the entire water system.

[0120] In order to test the corrosion inhibition effect of the corrosion inhibitor, the carbon steel sheet was ground and polished, washed with distilled water and anhydrous ethanol, and then dried. The initial mass m0 was weighed and recorded. Then it was put into the circulating water system of each test group to react for 48 hours. The surface corrosion products were taken out and cleaned, and then dried. The mass after corrosion m1 was weighed again and recorded. The corrosion rate η = (m0-m1) / m0×100% was calculated. The results are shown in the table below.

[0121] Table 1

[0122]

[0123] It can be seen from the blank group that the corrosion rate is the highest when no corrosion inhibitor is added, and the carbon steel sheet is severely corroded; the corrosion inhibitors of Comparative Examples 1 and 2 have certain corrosion inhibition effects, but are significantly worse than those of the embodiments of the present invention. The corrosion inhibitor of the present invention shows excellent corrosion inhibition effects under different water quality conditions. With the increase of water temperature and corrosive medium concentration, the corrosion inhibitor in Example 3 can still effectively inhibit corrosion, indicating that it has strong applicability in high temperature and high salt environments.

[0124] The above embodiments are merely examples for clear explanation, and are not intended to limit the implementation methods. For those skilled in the art, other different forms of changes or modifications can be made based on the above descriptions. It is not necessary and impossible to list all the implementation methods here, and the obvious changes or modifications derived therefrom are still within the protection scope of the invention.

Claims

1. A green and environmentally friendly pH-responsive corrosion inhibitor, characterized in that: The invention comprises the following raw materials in parts by weight: 25-30 parts of green tea polyphenols, 10-15 parts of graphene oxide nanosheets, 15-25 parts of pH-responsive polymer corrosion-inhibiting microcapsules, 5-10 parts of beta-cyclodextrin / corrosion-inhibiting salt inclusion compound, 5-10 parts of amino acid-derived polymer, 3-5 parts of thickener, 180-450 parts of solvent, and 0.01-0.05% of the total weight of the above raw materials as an antioxidant, and a pH regulator for adjusting the pH of the corrosion inhibitor to 7-8; the pH-responsive polymer corrosion-inhibiting microcapsules are microcapsules formed by using zinc salt and molybdate as capsule cores and hydrophobic pH-responsive polymer as capsule walls.

2. The green and environmentally friendly pH-responsive corrosion inhibitor according to claim 1, characterized in that: The preparation method of the pH-responsive polymer corrosion-inhibiting microcapsules comprises the following steps: 1) dissolving a hydrophobic pH-responsive polymer in an organic solvent, and then adding zinc salt and molybdate and mixing them evenly to form an oil phase; 2) dissolving the emulsifier in water and adjusting the pH of the solution to 7-8 to form an aqueous phase; 3) dropping the oil phase into the water phase and stirring at high speed for emulsification, then reducing the stirring speed for solidification, and finally separating the solid and the liquid, and drying the obtained solid to obtain pH-responsive polymer corrosion-inhibiting microcapsules.

3. The green and environmentally friendly pH-responsive corrosion inhibitor according to claim 2, characterized in that: The hydrophobic pH-responsive polymer is one of polyacrylic acid, polylactic acid-glycolic acid copolymer, polymethyl methacrylate, and polyethylene oxide-polylactic acid copolymer; the organic solvent is one of dichloromethane and ethyl acetate; the zinc salt is one of zinc acetate and zinc sulfate; the molybdate is one of sodium molybdate and ammonium molybdate; and the emulsifier is one of polyvinyl alcohol and polyethylene glycol.

4. The green and environmentally friendly pH-responsive corrosion inhibitor according to claim 2, characterized in that: In the oil phase, the mass concentration of the hydrophobic pH responsive polymer is 100-200 g / L, the mass concentration of the zinc salt is 30-50 g / L, and the mass concentration of the molybdate is 30-50 g / L; in the water phase, the mass concentration of the emulsifier is 10-20 g / L; and the volume ratio of the oil phase to the water phase is 1:(5-8).

5. The green and environmentally friendly pH responsive corrosion inhibitor according to claim 2, characterized in that: In the oil phase, the stirring speed of the emulsification process is controlled to be 800-1200 rpm, the emulsification temperature is 25-30° C., and the emulsification time is 10-20 min; the stirring speed of the solidification process is controlled to be 400-600 rpm, the solidification temperature is 25-27° C., and the solidification time is 2-3 h.

6. The green and environmentally friendly pH-responsive corrosion inhibitor according to claim 1, characterized in that: The preparation method of the β-cyclodextrin / corrosion-inhibiting salt inclusion compound comprises the following steps: 1) dissolving β-cyclodextrin in water to form a cyclodextrin solution, and then adding a corrosion-inhibiting salt and stirring thoroughly to form a mixed solution; 2) After adjusting the pH of the mixed solution to 5-7, heating and stirring are performed to carry out inclusion reaction, cooling after the reaction is completed, adding ethanol solution for precipitation, and drying the precipitate to obtain a β-cyclodextrin / corrosion inhibition salt inclusion complex.

7. The green and environmentally friendly pH-responsive corrosion inhibitor according to claim 6, characterized in that: The corrosion-inhibiting salt is one of zinc salt and molybdate; the mass ratio of the corrosion-inhibiting salt to β-cyclodextrin is (5-10):100; the reaction temperature of the inclusion reaction is 40-50°C, and the reaction time is 2-4h; the volume concentration of the ethanol solution is 50-70%, the volume of the ethanol solution is 1-1.5 times the volume of the mixed solution, and the precipitation time is 1-2h.

8. The green and environmentally friendly pH-responsive corrosion inhibitor according to claim 1, characterized in that: The sheet diameter of the graphene oxide nanosheet is 100nm~1μm; the particle size of the pH-responsive polymer corrosion-inhibiting microcapsule is 100nm~1μm; the particle size of the β-cyclodextrin / corrosion-inhibiting salt inclusion complex is 1~10μm; the amino acid-derived polymer is one of polyglutamic acid and polyaspartic acid; the thickener is carboxymethyl cellulose; the solvent is at least one of water and alcohol; the antioxidant is one of ascorbic acid and vitamin E; the pH adjuster is one of citric acid and sodium bicarbonate.

9. The method for preparing the green and environmentally friendly pH-responsive corrosion inhibitor according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1, adding an antioxidant to water, then heating it to 40-50° C., dissolving green tea polyphenols therein, and then adding β-cyclodextrin / corrosion-inhibiting salt inclusion complex and stirring thoroughly to obtain a first solution; S2, ultrasonically dispersing graphene oxide nanosheets in water or alcohol, adding the resultant to the first solution and stirring the solution sufficiently to obtain a second solution; S3, when the temperature of the second solution is controlled at 35-45°C, pH-responsive polymer corrosion-inhibiting microcapsules are added and stirred evenly, and then thickener and amino acid-derived polymer are added in sequence and stirred evenly, and finally the remaining solvent is added, and the pH of the solution is adjusted to 7-8 using a pH adjuster to obtain a green and environmentally friendly pH-responsive corrosion inhibitor.

10. Use of the green and environmentally friendly pH-responsive corrosion inhibitor according to any one of claims 1 to 8 in corrosion inhibition of water systems.

Citation Information

Cited By

  • Compound buffering agent for acidification in oil exploitation

    CN120005602A

  • Easily biodegradable phosphorus-free scale and corrosion inhibitor and preparation method thereof

    CN120328754A

  • Phosphorus-free environment-friendly grey water scale inhibition dispersant and preparation method thereof

    CN120463357A

  • Treatment method of high-pressure-resistant fracturing valve body

    CN120842947A